Morphological Perturbation of Human Erythrocytes Exposed to Photoilluminated Riboflavin - Iyad Ali; Imrana Naseem (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Background: Reactive oxygen species (ROS) are formed as a natural byproduct of the normal metabolism of oxygen and have important roles in cell signaling and homeostasis. However, during times of oxidative stress, ROS levels can rise dramatically. This may result in significant damage to cell structures. In this work we are interested to show the effect of different ROS on the morphology of fresh human RBCs. Methods: The RBCs were incubated with different reaction mixtures at room temperature and exposed to cool fluorescent light (800 lux). Then, cells were isolated and scanned by a scanning electron microscope. Results: When incubated with photoilluminated riboflavin, RBCs lost their biconcave shape and adopted a spherocytes shape. The formation of spherocytes is usually associated with spectrin deficiency. In the presence of Cu(II) and riboflavin, RBCs appeared with spikes of different sizes on their surface showing the formation of “acanthocytes”, which is usually prevalent in abetalipoprotienemia. Moreover, addition of NaN3 to riboflavin-Cu(II) system resulted in completely damaged RBCs. Away from the above combinations, when RBCs are incubated with riboflavin-aminophylline combination, they appeared with spikes of equal lengths and sizes on their surface “echinocytes”, which usually appear in different diseases like pyruvate kinase deficiency and uremia. Conclusion: Red blood cells undergo different morphological changes when incubated in each of the above combinations, most probably due to the formation of different ROS and these ROS could be involved in different pathological consequences.